Children and providers’ perspectives on once-weekly rifapentine and isoniazid TB preventive therapy - A.J. Marthinus; D.T. Wademan; Z. Saule; Y. Hirsch-Moverman; L. Viljoen; J. Winckler; L. van der Laan; M. Palmer; S.L. Barnabas; R. Boyd; A.C. Hesseling; G. Hoddinott (IJTLD Open)
BACKGROUND: TB preventive treatment (TPT) prevents the development of TB disease in individuals at risk of progression from infection to disease. However, implementation of TPT for children is poor in most high-burden settings. The long duration and pill burden of the 6-month once-daily isoniazid regimen (6H) pose significant barriers to completion. We aimed to understand children’s, caregivers’, and healthcare providers’ experiences of the 12-week once-weekly rifapentine and isoniazid (3HP) regimen using a dispersible tablet formulation in South Africa. METHODS: Serial, in-depth qualitative interviews with 20 child-caregiver dyads, including 5 children living with HIV (CLWH) and 9 healthcare providers across two study sites implementing a pharmacokinetic and safety trial of 3HP, were analysed deductively. RESULTS: Of those with experience using both 3HP and 6H, caregivers and healthcare providers preferred 3HP, and study participants reported that the 3HP formulation was more palatable and easier to prepare and administer. Caregivers and healthcare providers were concerned about optimally integrating 3HP into routine care, primarily due to its once-weekly administration. Children with HIV preferred the once-daily 6H regimen for its ease of use with their daily antiretroviral therapy. CONCLUSIONS: 3HP reduced the administration burden for children and their caregivers. Once weekly, 3HP dosing will require education and adherence support to ensure completion.